Corneal rat-to-mouse xenotransplantation and the effects of anti-CD4 or anti-CD8 treatment on cytokine and nitric oxide production - Pindjáková, Jana; Vítová, Andrea; Krulová, Magdaléna; Zajícová, Alena; Filipec, Martin; Holán, Vladimír (Transplant international, 2005)
Corneal xenotransplantation may be an alternative approach to overcome shortage of allografts for clinical transplantation. Orthotopic corneal rat-to-mouse xenotransplantation and syngeneic transplantation was performed and the effects of anti-CD4 and anti-CD8 treatments on corneal xenograft survival and production of cytokines, interleukin (IL)-2, IL-4, IL-10, gamma-interferon (IFN-gamma) and nitric oxide (NO) were evaluated. RT-PCR was used to determine the expression of genes for cytokines and inducible nitric oxide synthase (iNOS) in the grafts. The presence of iNOS protein in grafts was detected by immunofluorescent staining. We found that corneal xenotransplantation was associated with a strong upregulation of genes for both Th1 and Th2 cytokines and with NO production in the graft. Treatment of xenograft recipients with mAb anti-CD4, but not anti-CD8, resulted in a profound inhibition of IL-2, IL-4 and IL-10 production, and in a significant prolongation of corneal xenograft survival. The results show that upregulation of Th2 cytokines after corneal xenotransplantation does not correlate with xenograft rejection. Rather, corneal graft rejection is associated with the expression of genes for IFN-gamma and iNOS and with NO production.
Keywords: Rats; Nitric Oxide; zvířata; potkani inbrední LEW; Rats, Inbred Lew; Graft Survival; mužské pohlaví; synthasa oxidu dusnatého, typ II; Cytokines; transplantace heterologní; Mice, Inbred BALB C; cytokiny; myši; Mice; CD4 Antigens; Gene Expression; CD8 Antigens; myši inbrední BALB C; exprese genu; Corneal Transplantation; Nitric Oxide Synthase Type II; rohovka; Animals; Female; přežívání štěpu; Antibodies, Monoclonal; antigeny CD4; oxid dusnatý; antigeny CD8; synthasa oxidu dusnatého; transplantace rohovky; ženské pohlaví; Male; Transplantation, Heterologous; Cornea; krysa rodu Rattus; Nitric Oxide Synthase; monoklonální protilátky